RESPONSE TO THE RICHARD ERSKINES ARTICLE EARLY AFFECT CONFUSION: THE BORDERLINE BETWEEN DESPAIR AND RAGE - PART 1 OF A CASE STUDY TRILOGY - Grover E. Criswell; Maša Žvelc; Ray Little; James Allen (International Journal of Integrative Psychotherapy, 2012)
This article provides four responses from senior psychotherapists and supervisors to Erskine’s article Early Affect-Confusion: The “Borderline” Between Despair and Rage. The authors approach the first part of case study trilogy from their particular perspective and provide both challenge and respect for the author’s work.